TRIP PLANNER OVER PROBABILISTIC TIME-DEPENDENT ROAD NETWORKS - T, Reshmi.; Krishna, N.Santhana (IJRDO -Journal of Computer Science Engineering, 2016)
In recent times, themanagement of transportation systems hasturn into increasingly important in manyreal applications such as location-basedservices, traffic control, and so on. Theseapplications usually absorb queries overspatial road networks with energeticallychanging and complex traffic conditions. Inthis paper, we proposed such a network by aprobabilistic time-dependent graph referredas PT-Graph, whose edges are connectedwith uncertain delay functions. In this paperwe propose a functional query in the PTGraph,known as trip planner query (TPQ),which retrieves trip plans that traverse a setof query points in PT-Graph. To tackle theefficiency issue, we proposed the pruningmethods which include time interval pruningand probabilistic pruning to effectively ruleout false alarms of trip plans.